Solomon's secret arts : the occult in the age of enlightenment - Monod, Paul Kléber. (New Haven, Conn. ; London : Yale University Press, 2013)
The late 17th and 18th centuries are known as the Age of Enlightenment, a time of science and reason. But in this book Paul Monod reveals the surprising extent to which Newton, Boyle Locke, and other giants of rational thought and empiricism also embraced the spiritual, the magical, and the occult. Although public acceptance of occult and magical practices waxed and waned during this period they survived underground, experiencing a considerable revival in the mid-18th century with the rise of new anti-establishment religious denominations.
What was the occult? -- Aurora, 1650-1688 -- Eclipse, 1688-1760 -- Glad day, 1760-1815.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Occultism -- History -- 17th century; Occultism -- History -- 18th century; Enlightenment; Alchemy; Science -- history; Magic -- history; Alchemy; Occultism -- history; Occultisme -- Histoire -- 17e siècle.; Occultisme -- Histoire -- 18e siècle.; Siècle des Lumières.; Alchimie; alchemy; Enlightenment (18th-century western movement); BODY, MIND & SPIRIT -- Mysticism; BODY, MIND & SPIRIT -- Occultism; BODY, MIND & SPIRIT -- Parapsychology -- General; BODY, MIND & SPIRIT -- Reference; BODY, MIND & SPIRIT -- Supernatural; HISTORY -- Europe -- Great Britain; Enlightenment; Occultism; 1600-1799; Trivia and miscellanea; History